منهج القاضي أبي بكر بن العربي في عرض القراءات من خلال كتابه أحكام القرآن - الجعيد، سامي بن مسعود (عبد الفتاح محمود ادريس, 2016)
The idea of searching on display approach Imam Ibn al-Arabi in the readings, through his book, the Qur'an, in a statement on its position on the readings famous in terms of acceptance and response, and weighting them, also like him with readings anomalous and invoked the provisions and language, and reveals the search for his way of directing readings, and sources in the directive, as it shows the impact of the readings on the method of interpretation and doctrine and jurisprudence.
تقوم فكرة البحث على عرض منهج الإمام ابن العربي في القراءات القرآنية من خلال كتابه أحكام القرآن, وذلك ببيان موقفه من القراءات المتواترة من حيث القبول والرد, والترجيح بينها, ومثله أيضا مع القراءات الشاذة والاحتجاج بها في الأحكام واللغة, ويكشف البحث عن طريقته في توجيه القراءات, ومصادره في التوجيه, كما أنه يبين أثر القراءات على منهجه في التفسير والعقيدة والفقه.
Keywords: الفقهاء المسلمون -- أبوبكر بن العربي، محمد بن عبدالله بن محمد ، ت 543 هـ -- التراجم -- كتاب أحكام القرآن -- علم القرءات